INTRODUCTION TO NECESSITY THROUGH SHARIA AND LAW - Bayinat Basha Al Bajali, Abul Firdaus (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2018)
Worship includes every human movement in life, and accordingly, a person’s quest to take care of himself and his community is an obligation, and he is rewarded for it as long as he adheres to what he must do in it. Because the meaning of necessity is a comprehensive meaning that touches on many matters and a person must be characterized by reconciliation with himself and with others, and I have divided this research into issues preceded by an introduction. It included two topics. The first topic: in the definition of necessity in the language and in the terminology of legal jurists, and the second topic: it came in the definition of necessity according to the jurists of positive law, followed by a comparison between the two definitions. Then I interpreted the verses and explained the hadiths, criticism and deduction, and listed the opinions of scholars and tried to explain the most correct of it wherever it came. Using the analytical method, then it showed the teachings to which the verses guide us, which must be applied in dealing with people through the applied approach